Wpływ promieniowania uv na zmiany stężenia benzo-fluorantenów w ściekach = The effect of ultraviolet radiation on changes concentration of benzo-fluoranthenes in coking wastewater - Włodarczyk-Makuła, Maria; Turek, Agnieszka; Obstój, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to determine the effect of UV exposure time on the change in concentration of PAHs in industrial wastewater. The study was conducted with the use of coking wastewater collected from the outflow of biological wastewater treatment factory. Ultraviolet irradiation treatment plant was carried out using a variable exposure time: 30, 60 and 90 seconds. Quantification of PAHs was performed by liquid chromatography.
Keywords: naświetlanie UV; fotodegradacja; ścieki koksownicze; UV irradiation; photodegradation; cokingwastewater; Fl; B(j)F; B(b)F; B(k)F; HPLC